Transition-Metal-Free Terminal Alkyne Addition to Isatins - Dhara, Kalyan; Kapat, Ajoy; Ghosh, Tridev; Dash, Jyotirmayee (Synthesis, 2016)
A ‘direct’ alkynylation of isatins, which uses potassium tert-butoxide to provide the desired 3-hydroxy-3-ethynyl-2-oxindoles in good to high yields, is reported. This protocol proceeds smoothly for both electron-rich and electron-deficient alkynes in comparable reaction rates and does not require any specially design ligand or expensive transition-metal catalysts.
Keywords: alkynes; 3-hydroxy-3-ethynylindolin-2-ones; HIV; isatins; nucleophiles; addition; transition-metal-free